2013
DOI: 10.1016/j.freeradbiomed.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative DNA damage in mitochondrial dysfunction and Huntington’s disease pathogenesis

Abstract: Huntington’s disease (HD) is a neurodegenerative disorder with an autosomal dominant expression pattern and typically a late-onset appearance. HD is a movement disorder with a heterogeneous phenotype characterized by involuntary dance-like gait, bioenergetic deficits, motor impairment, and cognitive and psychiatric deficits. Compelling evidence suggests that increased oxidative stress and mitochondrial dysfunction may underlie HD pathogenesis. However, the exact mechanisms underlying mutant huntingtin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 143 publications
0
69
0
Order By: Relevance
“…A major by-product of ROS attack of genomic DNA is the pre-mutagenic lesion 8-OHdG, which results in G-to-T transversions [35]. The main defense against the mutagenic effect of 8-OHdG is the base excision repair pathway, which, in eukaryotes, is initiated by the OGG1 protein, a DNA glycosylase that catalyzes the excision of 8-OHdG from DNA [36]. Improper or incomplete repairs of DNA damage due to oxidative stress may result in DNA strand breaks, cell cycle arrest, apoptosis, and mitochondrial dysfunction, which in turn increases ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…A major by-product of ROS attack of genomic DNA is the pre-mutagenic lesion 8-OHdG, which results in G-to-T transversions [35]. The main defense against the mutagenic effect of 8-OHdG is the base excision repair pathway, which, in eukaryotes, is initiated by the OGG1 protein, a DNA glycosylase that catalyzes the excision of 8-OHdG from DNA [36]. Improper or incomplete repairs of DNA damage due to oxidative stress may result in DNA strand breaks, cell cycle arrest, apoptosis, and mitochondrial dysfunction, which in turn increases ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…12 During replication, cytosine or adenine bases incorporate into 8-OHdG resulting in guanine-cytosine thymine-adenine mismatch, and 8-oxoguanine glycosylase (OGG1) of the BER system repairs 8-OHdG lesions. 37,38 While DNA polymerase beta is responsible for incorporating the correct base in the nuclear DNA, POLG is important for the mtDNA. 13,39,40 In the pathogenesis of diabetic retinopathy, 8-OHdG levels are elevated and OGG1 accumulation in the mitochondria is attenuated, mtDNA damage is more extensive at the D-loop region than other regions of mtDNA, and the binding of POLG at the D-loop region is compromised and mtDNA transcription is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…As a structural analogue of succinate, 3-NPA covalently and irreversibly binds to the active site of the enzyme thereby preventing complex-II-mediated FADH 2 generation [17]. In neurological research, in which 3-NPA is widely used to damage dopaminergic neurons in animal models of HD or Parkinson's disease [18,19], it has been suggested that the mechanism underlying 3-NPA toxicity involves increased production of reactive oxygen species (ROS) [20].…”
Section: Introductionmentioning
confidence: 99%